A Systematic review and meta-analysis on the role of palliative primary resection for pancreatic neuroendocrine neoplasm with liver metastases. Issue 3 (March 2018) - Partelli, Stefano; Cirocchi, Roberto; Rancoita, Paola M.V.; Muffatti, Francesca; Andreasi, Valentina; Crippa, Stefano; Tamburrino, Domenico; Falconi, Massimo
Abstract: Background: Role of palliative pancreatic neuroendocrine neoplasm (PanNEN) resection (pPanNEN-R) is controversial. This study was designed as a meta-analysis of studies which allow a comparison of pPanNEN-R and non-surgical management (PanNEN-nR). Methods: All published studies until 2017 allowing for the comparison of pPanNEN-R and PanNEN-nR were reviewed. Primary outcome was overall survival (OS). Secondary outcomes measures included postoperative morbidity, reoperation, readmission, length of hospital stay (LOS), and quality of life (QoL). Risk of death was compared by computing the odds-ratio (OR), while 5- and 10-year OS using weighted mean differences. Results: Seven studies were included. A total of 885 patients were included, of whom 252 (28%) underwent pPanNEN-R and 633 (72%) underwent PanNEN-nR. Overall quality of included studies was fair. The risk of death was significantly reduced in patients who underwent pPanNEN-R compared to those who underwent PanNEN-nR (OR = 0.38, 95% CI 0.23–0.65). Data on postoperative morbidity, reoperation, readmission, LOS, and QoL were not adequately reported therefore a meta-analysis for the secondary outcomes was not performed. Discussion: pPanNEN-R in patients with unresectable LM seems to be associated with a better OS compared to non-surgical management but the limitations of included studies does not allow firm conclusions.